Electroderaeous crassicornis, a new genus and species of Deraeocorinae (Hemiptera: Heteroptera: Miridae) in Miocene Dominican amber - Taszakowski, Artur; Kim, Junggon; Bonino, Enrico; Tettamanzi, Lorenzo; Jung, Sunghoon (Zootaxa, 2023)
The third fossil record of a deraeocorine species, preserved as an inclusion in late Lower Miocene, Burdigalian amber from Hispaniola (Dominican Republic) is presented with a description of Electroderaeous crassicornis gen. and sp. nov. based on a well-preserved specimen.